The Use of Information Technology in Environmental Management: The Case of Brazilian Amazon Forest - Pereira, Rodrigo M.; Júnior, Celso Vila Nova de S.; Moreira, Tito Belchior S. (Journal of Environmental Accounting and Management, 2026)
In the mid 2000's the Brazilian Government introduced a new environmental policy to reduce deforestation in the ``Plan for Prevention and Control of Legal Amazon Deforestation'', (PPCDAM). With 14 years of track record, heavily relying on technological innovation, the policy is nowadays considered a major example of success in the overall war waged against the deforestation of tropical rainforests. In this paper we quantify this success. The results suggest that the policy not only had a direct effect of reducing deforestation, but also rendered deforestation less sensitive to fluctuations in the Amazon commodity production, which can be considered our academic contribution to this paper. We also perform a counterfactual exercise, estimating the levels of deforestation that would have been registered, had the policy not existed. We estimate that the plan saved a total of 196 thousand square kilometers of forest between 2005 and 2015, corresponding to almost twice the total amount of deforestation observed during this period, and 4.9% of the entire Brazilian Amazon Forest.